Strategy of using Meohai Gymnastics Practice on the Risk of Cardiovascular System (CVS) - Wahida; Sultina Sarita; Hesti Resyana; Tinuk Esti Handayani; Fitriyanti Fitriyanti (Postgraduate, University of Mataram, 2025)
This study aims to evaluate the effects of the Meohai exercise program intervention on health indicators, especially on blood pressure, cholesterol profile, and Body Mass Index in postmenopausal women. The method used was quasi-experimental study with pretest-posttest approach involving 60 respondents from Mekar and Leppe Villages in Konawe, Indonesia. All respondents underwent Meohai training for 3 months, with frequency of twice a week, under the guidance of professional instructor. The results of the analysis showed that 93.3% of respondents experienced normalization of blood pressure after the intervention, with p value <0.000. The average cholesterol profile decreased from 239.40 mg/dL to 139.23 mg/dL (p = 0.002), and BMI decreased from 27.41 to 24.67 (p = 0.007). These findings indicate that the Meohai exercise program is effective in improving cardiovascular health in postmenopausal women, and emphasize the importance of lifestyle modification, including regular physical activity, as strategy for the prevention and management of cardiovascular disease risk. The association between decrease in blood pressure, cholesterol, and BMI underscores the need for a comprehensive approach to health intervention design. This study provides empirical evidence that can form the basis for health programs to improve community well-being, especially in vulnerable populations such as postmenopausal women.